Navigating the Direction of Tradition Change: A Case Study on the Si Muntu Parade Tradition in West Sumatra - Saaduddin, Saaduddin (Melayu Arts and Performance Journal, 2023)
The tradition of the Si Muntu procession is an integral part of the cultural life of the people of West Sumatra. However, like local traditions in various regions in Indonesia, the Si Muntu Procession has also experienced significant development and transformation in the face of globalization. This article aims to understand the development and transformation of this tradition in the context of globalization by conducting a case study in West Sumatra. Using library data and field data, all analyzes were carried out descriptively.